Effect of the addition of Chaetoceros calcitrans, Navicula sp. and Phaeodactylum tricornutum (diatoms) on phytoplankton composition and growth of Litopenaeus vannamei (Boone) postlarvae reared in a biofloc system. (8th December 2016) - Marinho, Yllana Ferreira; Brito, Luis Otavio; Silva Campos, Clarissa Vilela Figueiredo da; Severi, William; Andrade, Humber Agrelli; Galvez, Alfredo Olivera
Abstract: The aim of this study was to evaluate the effect of the addition of Chaetoceros calcitrans, Navicula sp. and Phaeodactylum tricornutum (diatoms) on phytoplankton composition and the growth of Litopenaeus vannamei postlarvae reared in a biofloc system. Four treatments were used: BFT (biofloc system without feed and no addition of diatoms); BFT‐F (biofloc system with feed and no addition of diatoms); BFT‐D (biofloc system with the addition of diatoms and no feed); and BFT‐FD (biofloc system with the addition of feed and diatoms), all in triplicate. The shrimp (16 ± 0.02 mg) were stocked at 2500 postlarvae m −3 and fed a commercial feed. Diatoms were added on the 1st, 5th, 10th and 15th day at a density of 5 × 10 4 cells mL −1 for each species. No significant differences ( P  >   0.05) between treatments were observed for gross primary production, net ecosystem production and water column respiration rate. However, significant differences ( P  <   0.05) were observed for nitrite, orthophosphate, alkalinity, final weight, weight gain, yield, feed conversion ratio (FCR), phytoplankton and cyanobacteria composition. The BFT‐FD treatment had better performance parameters for final weight (270 mg), weight gain (254 mg), yield (0.67 Kg m −3 ) and FCR (0.61), indicating the benefits of the diatoms C. calcitrans, Navicula sp. and P. tricornutum for decreasing cyanobacteria and improving growth of L. vannamei postlarvae reared in biofloc systems.